1981
DOI: 10.1093/nar/9.1.213-b
|View full text |Cite
|
Sign up to set email alerts
|

Codon catalog usage is a genome strategy modulated for gene expressivity

Abstract: The nucleic acid sequence bank now contains 161

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
456
2
2

Year Published

1989
1989
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 924 publications
(483 citation statements)
references
References 41 publications
23
456
2
2
Order By: Relevance
“…To isolate full-length Spin cDNA from gibel carp, we designed four degenerate primers: skr1, skr2, skf1 and skf2 (Table 1) based on the conserved motif sequences of Spin/Ssty protein family and also the amino acid usage rates in fish proteins (Grantham et al, 1980(Grantham et al, , 1981. An about 250 bp fragment was amplified by Nested PCR from SMART cDNA library of gibel carp mature eggs, and was shown to have high similarity to human and mouse Spin gene.…”
Section: Cdna Cloning and Sequence Characterization Of Gibel Carp Spimentioning
confidence: 99%
“…To isolate full-length Spin cDNA from gibel carp, we designed four degenerate primers: skr1, skr2, skf1 and skf2 (Table 1) based on the conserved motif sequences of Spin/Ssty protein family and also the amino acid usage rates in fish proteins (Grantham et al, 1980(Grantham et al, , 1981. An about 250 bp fragment was amplified by Nested PCR from SMART cDNA library of gibel carp mature eggs, and was shown to have high similarity to human and mouse Spin gene.…”
Section: Cdna Cloning and Sequence Characterization Of Gibel Carp Spimentioning
confidence: 99%
“…CAC CAG CAT CAG GTA GTG GAT GGG GTT CAG CAT CTC CAG CAC-3 '; 35mer, 5 '-TT CTG GAT GCT CTC CAC ACA CTG GCC CTG CAG GGT-3') were synthesized by the modified triester method [16]. The base sequences of both probes were designed on the basis of partial amino acid sequences of human placental P'45OAaoM [17], using published data for codon usage frequencies [18]. All other materials including restriction endonucleases, [c+32P]dCTP and [y-'*P]ATP were obtained from commercial sources.…”
Section: Cdna Clonesmentioning
confidence: 99%
“…Grantham's genome hypothesis proposes that each species systematically uses certain synonymous codons (codons that code for the same amino acid) in coding sequences (2)(3)(4), in other words, that each species has a distinct codon bias. Many studies have since confirmed that, at least in prokaryotes, selective forces acting at the level of translation maintain biased codon usage (5)(6)(7).…”
mentioning
confidence: 99%
“…In contrast, explanation ii is referred to as a neutral or mutational explanation. Variation in codon bias among genes from the same organism has been shown to depend on many parameters, including expression level (4,5,11), amino acid composition (12)(13)(14)(15), gene length (16,17), mRNA structure (18)(19)(20), and protein level noise considerations (21). In most of these cases, evidence exists that selection at different steps during protein expression shapes codon bias.…”
mentioning
confidence: 99%